FACTORS INFLUENCING THE ADOPTION BEHAVIOUR OF FISH FARMERS TOWARDS SCIENTIFIC FISH CULTURE - GOSWAMI, BISWAJIT (Journal of the Inland Fisheries Society of India, 2021)
This paper analyses the factors influencing adoption behaviour of fish farmers towards scientific fish culture practices in Dakshin Dinajpurdistrict of West Bengal. The data were collected through interview method following a structured schedule from 120 fish farmersselected randomly. Both qualitative and quantitative variables were used for getting results on adoption technique. The findings revealed that the majority of the farmers have obtained medium adoption score(71.3). Out of 24 variables included in the study, 14 variables were positively and significantly related with adoption level of fish farmers. Technique of Path analysis showedthat knowledge about scientific fish culture exhibited highest positive direct effect on adoption behaviour of fish farmers followed by extension agency contact, innovative proneness, extent of weed infestation and economic motivation. Key words: Fish farmers, adoption behaviour, factors, scientific fish culture.